A study on glabellar wrinkle patterns in Koreans. (30th October 2013) - Kim, H.S.; Kim, C.; Cho, H.; Hwang, J.Y.; Kim, Y.S.
Abstract Background Botulinum toxin is a well‐established treatment for dynamic glabellar lines. The glabella is in fact, the most common site for botulinum toxin injection in Asians. Previous studies have identified five glabellar contraction patterns according to the predominance of eyebrow approximation, depression or elevation. Unfortunately, the authors found the former classification somewhat confusing. Objective To identify and classify glabellar wrinkle patterns in Koreans for a better treatment approach. We also aimed to provide an Asian consensus recommendation for the individual wrinkle pattern. Methods A retrospective photographic analysis of 139 Korean patients who received botulinum toxin for the first time to treat glabellar wrinkles was conducted. The wrinkle patterns were identified and classified by a panel of experienced Korean dermatologists, based on the prevalence of perpendicular and transverse glabellar lines, the nasal wrinkles and the forehead wrinkles. The panel also convened to develop a clinical consensus on the individual wrinkle pattern in Asians. Results Five patterns were identified: (1) 'U', (2) '11′, (3) 'X', (4) 'π (Phi)' and (5) 'I'. The classification method allowed indentifying the most important muscles in each wrinkle pattern. The consensus recommendation addressed the most heavily used muscles to receive higher doses and to be injected into a larger number of sites. Those less solicited muscles were left untreated or received lower doses, allowing for more effective and natural results. Conclusion Interpersonal differences in facial animation exist among Koreans. We hope our simple glabellar wrinkles classification enables a more accurate, individualized treatment with botulinum toxin in Asians.